A Matlab Tool for Tumor Localization in Parathyroid Sestamibi Scintigraphy - M. Đurović; M. M. Jankovic; A. Koljević Marković (Telfor Journal, 2015)

(untitled)
Submarine method for localization of parathyroid tumors (PT) has proved to be effective in case of typical pitfalls of conventional scintigraphic methods (combined subtraction and double phase methods). It uses images obtained by standard dynamic parathyroid sestamibi scintigraphy suggested by European Association of Nuclear Medicine. This paper presents: 1) the developed Matlab interface that enables the implementation and evaluation of algorithms for the automatic application of Submarine method; 2) the algorithm for automatic extraction of the entire thyroid region from the background radioactivity using operations from mathematical morphology applied on dynamic scintigrams; 3) the results obtained by algorithm for localization and visualization of PTs based on estimation of exponential decreasing trend of time-activity curves. The algorithm was tested on a group of 20 patients with histopathologically proven PTs using developed Matlab interface.